2022
DOI: 10.1016/j.cell.2022.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Receptor binding and complex structures of human ACE2 to spike RBD from omicron and delta SARS-CoV-2

Abstract: COVID-19 pandemic continues worldwide with many variants arising, especially those of variants of concern (VOCs). A recent VOC, Omicron (B.1.1.529), which obtains a large number of mutations in the receptor-binding domain (RBD) of the spike protein, has risen to intense scientific and public attention. Here we studied the binding properties between the human receptor ACE2 (hACE2) and the VOC RBDs and resolved the crystal and cryo- EM structures of the Omicron RBD-hACE2 complex, as well as the crystal structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
466
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 441 publications
(545 citation statements)
references
References 64 publications
43
466
2
Order By: Relevance
“…Delta mutations, L452R front of the neck, T478K far side of left shoulder, fall just peripheral to the ACE2 binding footprint (Figure 1A) (Han et al, 2022). Omicron shares at least one RBD mutation with all of these variants.…”
Section: Resultsmentioning
confidence: 95%
“…Delta mutations, L452R front of the neck, T478K far side of left shoulder, fall just peripheral to the ACE2 binding footprint (Figure 1A) (Han et al, 2022). Omicron shares at least one RBD mutation with all of these variants.…”
Section: Resultsmentioning
confidence: 95%
“…Alarmingly, the Omicron variant carries an unusual number of mutations, particularly on the spike (S) protein including the receptor-binding domain (RBD), which might lead to altered transmissibility and immune escapes [2] . Population-level evidence showed an association between the emergence of Omicron and a higher risk of reinfection, indicating its ability to evade immunity from prior infection [1] .…”
Section: Omicron Spread Around the Worldmentioning
confidence: 99%
“…Moreover, a recent study demonstrated that K417N mutation led to reduced cellular immune responses [8] . However, structural analysis showed that K417N might moderately decrease binding affinity of human ACE2 [2] , indicating an evolutionary trade-off between infectivity and immune escape.…”
Section: Omicron Escapes Many Commercially Available Neutralizing Antibodiesmentioning
confidence: 99%
See 1 more Smart Citation
“…As of yet, binding strength differences of SARS-CoV-2 VOCs' spike proteins to hACE2 are estimated controversially, depending on molecular modelling and simulation approaches [19][20][21][22][23][24]. Experimental data on binding strengths of SARS-CoV-2 Omicron's spike protein to hACE2 which so far have become available provide evidence that Omicron's RBD interaction with hACE2 is weaker than that of Delta's RBD [25][26][27], with one exception which states that binding strength of Delta's or Omicron's RBD to hACE2 was in similar ranges [28].…”
Section: Variant Of Concern and Human Bindingmentioning
confidence: 99%